Confronting the democratic discourse of librarianship - Popowich, Sam (Library Juice Press, 2019)
The democratic discourse of librarianship – Vectors of oppression – Liberalism and the enlightenment – Ideology and hegemony in the Marxist tradition – Three hegemonies of library history – The library myth – Truth machines: the political economy of command and control – Dual power and mathesis – Conclusion: lives and time.
Includes bibliographical references and index
Keywords: Libraries and society; Libraries; Library science; Libraries and state